Designing A Catalog Management System– An Ontology Approach - Farsani, Hadi Khosravi; Nematbakhsh, Mohamad Ali (Malaysian Journal of Computer Science, 2007)
When enterprises collaborate, a common frame of understanding of all products and catalogs in each organization is indispensable. Suppliers who virtually collaborate should be able to share product related data, create new products, and update old products from their own catalog. In this paper, we describe the development of a model for presenting electronic catalog based on OWL ontology language. This model uses WordNet ontology to distinguish classes and the relationships between them. We use SPARQL query language to introduce three types of search for the catalog management system. The concepts of this classification system are mapped to the concept of current standard classification systems such as UNSPSC, ECL@SS, and etc. We use VSM to diagnose class of one product. For customization aspect of electronic catalog, we introduce a semantic recommendation procedure which is more efficient when applied to Internet shopping malls. The suggested procedure recommends the semantic products to the customers and is originally based on Web usage mining, product classification, association rule mining, and frequently purchasing. We applied the procedure to the data set of MovieLens Company for performance evaluation, and some experimental results are provided. The experimental results have shown superior performance in terms of coverage and precision.